Modelling of Critical Acceleration for Regional Seismic Landslide Hazard Assessments by Finite Element Limit Analysis - Li, Cheng; Wei, Shuhe; Xu, Xingqian; Qu, Xin (Frontiers in Earth Science, 2022)
The critical acceleration model plays an important role in seismic slope stability and determines the predictive accuracy of regional seismic landslide hazard assessments. Recently, the critical acceleration model based on the limit equilibrium method has been used to evaluate the seismic stability of regional slopes. However, when the Hoek-Brown failure criterion is used to evaluate the seismic stability of slopes with angles greater than 60°, the results obtained is unconservative by limit equilibrium method. Therefore, based on the simulation of a typical slope model with finite element limit analysis, prediction equations of the critical acceleration are established. The corresponding results are compared with the prediction results from the limit equilibrium method. This comparison shows that the proposed critical acceleration model has higher predictive accuracy than the limit equilibrium method, especially when the Hoek-Brown failure criterion is used to evaluate the slopes with angles greater than 60°. The proposed model is applicable to the global scope and can be effectively applied to regional seismic landslide hazard assessments.